Attachment theory within clinical supervision: application of the conceptual to the empirical. Issue 1 (2nd January 2017) - Wrape, Elizabeth R.; Callahan, Jennifer L.; Rieck, Troy; Watkins, C. Edward
Abstract : Attachment theory, which has demonstrated application in caregiver-child, romantic, and psychotherapeutic relationships, also appears to be supervision relevant. But bad blood between attachment theory and psychoanalysis may well have hampered considering the relevance of attachment theory for psychoanalytic supervision. This project sought to investigate the application of attachment theory to the supervision situation, with the potential implications of our findings for psychoanalytic supervision being considered. Attachment styles, leader–follower dynamics, and attachment-based expectations were explored as predictors of supervisor-trainee working alliance using a prospective, longitudinal study design. Findings revealed the importance of measuring supervision-specific attachment, the particularly problematic nature of supervisee avoidant attachment, and the potential contribution of a leader–follower framework for understanding supervisory attachment. These attachment concepts may well be useful in, and additive for, psychoanalytic supervision practice.